AKTUALISASI DIRI PADA PENCAPAIAN TUJUAN PENDIDIKAN ISLAM DALAM PENGEMBANGAN KETERAMPIAN SOFT SKILL - Ahmad Zain Sarnoto; Laela Fitriyani (PMPP Lembaga Penelitian dan Studi Kebijakan, 2020)
Succesfull and achievement of a person in various aspects of life is not determined solely by academic knowledge and technical skill (hard skill). But more to the ability to manage yourself and others ( soft skill). This is in line with what was stated by Patton, who stated